Characterization of Chemical Compounds with Antioxidant and Cytotoxic Activities in Bougainvillea x buttiana Holttum and Standl, (var. Rose) Extracts - Rodolfo Abarca-Vargas; Carlos F. Peña Malacara; Vera L. Petricevich (MDPI AG, 2016)
Bougainvillea is widely used in traditional Mexican medicine to treat several diseases. This study was designed to characterize the chemical constituents of B. x buttiana extracts with antioxidant and cytotoxic activities using different solvents. The extraction solvents used were as follows: distilled water (dH2O), methanol (MeOH), acetone (DMK), ethanol (EtOH), ethyl acetate (EtOAc), dichloromethane (DCM), and hexane (Hex) (100%) at an extraction temperature of 26 °C. Analysis of bioactive compounds present in the B. x buttiana extracts included the application of common phytochemical screening assays, GC-MS analysis, and cytotoxicity and antioxidant assays. The results show that the highest extraction yield was observed with water and methanol. The maximum total phenolic content amount and highest antioxidant potential were obtained when extraction with methanol was used. With the exceptions of water and ethanol extractions, all other extracts showed cytotoxicity ranging between 31% and 50%. The prevailing compounds in water, methanol, ethanol, and acetone solvents were as follows: 4H-pyran-4-one, 2,3-dihydro-3, 5-dihydroxy-6-methyl (2), 2-propenoic acid, 3-(2-hydrophenyl)-(E)- (3), and 3-O-methyl-d-glucose (6). By contrast, the major components in the experiments using solvents such as EtOH, DMK, EtOAc, DCM, and Hex were n-hexadecanoic acid (8), 9,12-octadecadienoic acid (Z,Z) (12); 9-octadecenoic acid (E)- (13), and stigmasta-5,22-dien-3-ol (28).